Federal directives, local discretion and the majority rule - Antoine Loeper (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2010)
We consider a federation in which citizens determine by federal majority rule a discretionary policy space which partially restricts the sovereignty of member states. Citizens first vote on the size of the discretionary space (the degree of local discretion), and then on its location on the policy space (the federal directive). Finally, each state votes on its respective policy within the discretionary space. This federal mechanism allows voters to express directly their trade-off between flexibility and policy harmonization. We show that at the voting equilibrium, the federal directive is negatively sensitive to the preferences of nonmedian voters. Moreover, the degree of local discretion is too limited and insufficiently sensitive to the magnitude of externalities. Hence, the model shows that inadequate and excessively rigid federal interventions can emerge from a neutral and democratic decision process without agency costs or informational imperfections.
Keywords: H77; D72; 330; Federalism; Local Discretion; Directive; Partial Decentralization; Majority rule